2013
DOI: 10.1063/1.4775684
|View full text |Cite
|
Sign up to set email alerts
|

Damping of CoxFe80−xB20 ultrathin films with perpendicular magnetic anisotropy

Abstract: We use vector network analyzer ferromagnetic resonance to study the perpendicularly magnetized CoFeB films. We report the dependence of the anisotropy, the g-factor, and the damping upon the Fe-Co compositional ratio in the amorphous and crystalline states. The damping and the anisotropy increase upon crystallization but vary little with composition on the Fe-rich side. At high cobalt content, the anisotropy lowers while the damping and the sample inhomogeneity increase. The compositional dependences seem to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 20 publications
15
90
1
1
Order By: Relevance
“…The solid lines correspond to the (thicker) films with hcp(0001)-dominated structure and the dashed lines are fits to the (thinner) fcc(111)-dominated phase for Cu and Ir overlayered films. The α 0 were extracted from the intercepts, and are shown in Table I; these agree well with literature values for bulk hcp Co [30], and a recent theoretical prediction for bulk fcc Co [29]. In principle, the slope of the fits shown in Fig.…”
Section: Fig 1 (Color Online)supporting
confidence: 64%
“…The solid lines correspond to the (thicker) films with hcp(0001)-dominated structure and the dashed lines are fits to the (thinner) fcc(111)-dominated phase for Cu and Ir overlayered films. The α 0 were extracted from the intercepts, and are shown in Table I; these agree well with literature values for bulk hcp Co [30], and a recent theoretical prediction for bulk fcc Co [29]. In principle, the slope of the fits shown in Fig.…”
Section: Fig 1 (Color Online)supporting
confidence: 64%
“…The effective perpendicular anisotropy field (µ 0 H eff k ) and the Gilbert damping constant (α) in [Co/Ni] was measured via vector-network-analyzer ferromagnetic resonance (VNA-FMR) 39 and corresponding analysis 40 . The effective perpendicular anisotropy energy (K eff U ) is calculated by the equation…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies reported on dopants that increase the damping when incorporated into a ferromagnetic film 40,54 . In our case, it is natural to expect that an impact from the diffused seed layer element will be exerted on the dynamic magnetic properties of [Co/Ni].…”
Section: Impact Of Diffusion On the Dynamic Magnetic Propertiesmentioning
confidence: 99%
“…Additionally, the amorphous CoFeB films would be expected to have a very low Gilbert damping coefficient down to 0.012 due to the homogeneity of the interfaces. 41 Low M s , high K u (very thin Bloch wall width) and low damping coefficient are desirable for creating spin-transfer torque devices working with low current density of spin-switching to compete with the other PMA thin films. 13,42 Regarding the magnetization reversal, the studied multilayer films would be very potential to apply to the domain-wall spin-torque devices, particularly, because the interfacial-supported domain nucleation and steady movement of the domain walls would be fruitful for simple control of domain walls motion.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%